Exploring semantic primes in the Karakalpak language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the concept of semantic primes within the Karakalpak language, a Turkic language spoken by the Karakalpak people in Central Asia. And learners can know some examples of semantic prime in the Karakalpak language. In addition to this, they can find the linguist who made a research about the semantic primes over the world.